The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep10147
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Therapy of Diabetes and Overall Cancer Risk and Mortality: A Meta-Analysis of 265 Studies

Abstract: Different anti-diabetic medications (ADMs) may modify cancer risk and mortality in patients with diabetes. We conducted a systematic review and meta-analysis to estimate the magnitude of association and quality of supporting evidence for each ADM. A total of 265 studies (44 cohort studies, 39 case-control studies, and 182 randomized controlled trials (RCT)) were identified, involving approximately 7.6 million and 137,540 patients with diabetes for observational studies and RCTs, respectively. The risk of bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 55 publications
(67 reference statements)
4
120
1
6
Order By: Relevance
“…A systematic review of observational studies suggested that diabetic patients on metformin have a reduction in the rate of CRC compared to their diabetic counterpart not on metformin [53, 6264]. Furthermore, a multicenter double-blind, randomized controlled phase III trial found that non-diabetic patients who received metformin 250 mg daily were less likely to have metachronous adenomas 1 year after polypectomy compared to those who received placebo (RR 0.67; 95% CI 0.47–0.97) [65].…”
Section: Treatment Considerations In Diabetes-related Enteropathic DImentioning
confidence: 99%
“…A systematic review of observational studies suggested that diabetic patients on metformin have a reduction in the rate of CRC compared to their diabetic counterpart not on metformin [53, 6264]. Furthermore, a multicenter double-blind, randomized controlled phase III trial found that non-diabetic patients who received metformin 250 mg daily were less likely to have metachronous adenomas 1 year after polypectomy compared to those who received placebo (RR 0.67; 95% CI 0.47–0.97) [65].…”
Section: Treatment Considerations In Diabetes-related Enteropathic DImentioning
confidence: 99%
“…Increasing evidence has demonstrated the anticancer capacity of metformin. A recent meta-analysis by Wu et al (36) in 2015 evaluated the use of metformin in patients with type 2 diabetes and indicated that this use was associated with 14 and 30% reductions in the rates of cancer incidence and mortality, respectively. Furthermore, other meta-analyses (37-40) obtained similar results, suggesting an overall decrease in the risk of cancer by metformin.…”
Section: Selection Comparability Outcome ----------------------------mentioning
confidence: 99%
“…Epidemiologic studies in patients with diabetes highlighted a positive association between the chronic consumption of metformin and a decrease in the incidence of various types of cancer [85][86][87], data further supported by a meta-analysis that confirmed the reduction of cancer risk and mortality in patients treated with metformin [88], thus encouraging the potential oncological use of this drug. Metformin effects have been evaluated in preclinical studies on different solid tumor models, including breast [89,90], endometrial [91], pancreatic [70], lung [92], prostate [93], head and neck [94] carcinomas, glioma and neuroblastoma [95][96][97], and blood malignancies [98][99][100].…”
Section: Metforminmentioning
confidence: 88%